Seven new species of Trigonopterus Fauvel (Coleoptera, Curculionidae) from the Tanimbar Archipelago - Narakusumo, Raden Pramesa (Zookeys, 2019)
Abstract. Based on recent fieldwork, the hyperdiverse weevil genus Trigonopterus Fauvel is recorded for the first time from the Indonesian Tanimbar Archipelago, halfway between Australia and Western New Guinea. All seven species discovered on Tanimbar are new to science, and described here: Trigonopterus atufsp. nov., T. kumbangsp. nov., T. laratensissp. nov., T. porgsp. nov., T. selaruensissp. nov., T. tanimbarensissp. nov., and T. triradiatussp. nov. The new species are authored by the taxonomists-in-charge, Raden Pramesa Narakusumo and Alexander Riedel. This fauna appears discordant and established by relatively recent dispersal from New Guinea and other Moluccan islands.